UPAYA PENANGGULANGAN GELANDANGAN DAN PENGEMIS (GEPENG) SEBAGAI PENYANDANG MASALAH KESEJAHTERAAN SOSIAL (PMKS) DI YOGYAKARTA - Fadri, Zainal (KOMUNITAS, 2019)
Vagrant and beggar are one of the social welfare problems currently spreading in urban areas and also began to spread in rural areas. Vagrant and beggar or commonly known as gepeng get daily-life needs by living and earning on the road, even spending a lot of time on the streets. Gepeng is often found in people's lives as beggars and often rises a troublesome because of their actions taken such as picking, grabbing, and robbing, so that proper handling must be carried out immediately. Preventions are carried out in order to create the security and convenience which is a way to provide livelihoods more feasible for them, especially in Yogyakarta. The method used in this paper is qualitative descriptive. Data is taken from using references and previous studies by conducting informal interviews as a approach form gepeng on their activities. The result of this research shows that gepeng has different characteristics from the common street cases, then the handling of gepeng should be taking a different approach. Handling gepeng by the government, the private sector and the community in an integration will certainly have a positive impact on gepeng mitigation, and it has been carried out in Yogyakarta even though it has not overcome the problem completely.